2001
DOI: 10.1007/s002470100515
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric pelvic imaging: improvement in gonad shield placement by multidisciplinary audit

Abstract: Audit was an effective tool in gaining the resources needed to improve technique and reduce radiation exposure in children. The multidisciplinary approach was vital in the success of this project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The reasons why the neonates at our hospital experienced more gonad exposure were the lack of awareness about the effect of radiation on the gonads, the fact that neonates move rapidly, and technicians forgetting to shield the gonads during radiography. One study showed that the dose received by the gonads can be reduced by 30 to 40% if the shield containing lead equivalent material is correctly placed (McCarty et al, 2001). In other words, the "as low as reasonably achievable" principle should be kept in mind, and new landmarks need to be identified to ensure that essential diagnostic information is obtained while the gonads are accurately protected.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons why the neonates at our hospital experienced more gonad exposure were the lack of awareness about the effect of radiation on the gonads, the fact that neonates move rapidly, and technicians forgetting to shield the gonads during radiography. One study showed that the dose received by the gonads can be reduced by 30 to 40% if the shield containing lead equivalent material is correctly placed (McCarty et al, 2001). In other words, the "as low as reasonably achievable" principle should be kept in mind, and new landmarks need to be identified to ensure that essential diagnostic information is obtained while the gonads are accurately protected.…”
Section: Discussionmentioning
confidence: 99%
“…The placement of such modern shields is often inaccurate, and an unfortunate consequence of misplacement is obscuration of critical orthopaedic landmarks [12][13][14][15][16]18]. The application of shields can be especially difficult in children.…”
Section: Discussionmentioning
confidence: 99%
“…The application of shields can be especially difficult in children. The audit process and radiographer training reportedly have an inconsistent and disappointing impact on the degree of accuracy, perhaps reflecting, in part, the training challenges faced in large departments with significant staff turnover [13,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality assurance program should also perform regular tests to all machinery involved with the delivery of radiation burden, and should organize audits to ensure that DRL are kept regarding diagnostic tests in pediatrics as well as in all imaging procedures involving radiation exposure. All departments can benefit from audits and re-evaluation and standardization of their procedures [28,50,51,52,53].…”
Section: Radiation Protection Considerations During Diagnostic X-ray mentioning
confidence: 99%